Challenges in the Dryland Agricultural Production Systems of South Asia: Research Priorities and Strategies - Haileslassie, Amare; Craufurd, Peter (Annals of Arid Zone, 2016)
Dryland (arid and semi-arid) ecosystems occupy more than 41% of global land area and are home to 2.5 billion people. More than 50% of South Asia’s dryland ecosystems are located in India. Drylands contribute about 40% of the total food grain production and support two-thirds of livestock population. Despite these important roles, agricultural production systems in the drylands are facing numerous challenges that threaten their resilience and future sustainability. This paper demonstrates some of the challenges and draws implications for priorities research and strategies. As an example, we selected districts representing different dryland agricultural production systems in western Rajasthan, Andhra Pradesh and Karnataka states of India. First we focus on the present performance of the major agricultural production systems by highlighting their structure (e.g. farm size) and key indicators of their function and state (e.g. production). We discuss major problems in terms of their cause and effect on these systems’ structure and function. Finally we synthesize lessons as to where system research should focus and what strategies are needed to produce a more resilient and dryland sustainable agricultural production system in in the future.